Investigation of the Pressure Drop of Random Packed Bed Adsorbers - B. Haddadi; C. Jordan; H.R. Norouzi; M. Harasek (Chemical Engineering Transactions, 2016)
Adsorption is one of the most often used unit operations in chemical engineering. However, due to computational limitations and time constraints simulations of adsorption processes are commonly done only with black box models or simplified porous media structures. In a new project an OpenFOAM® based CFD solver adsorpFoam, the required grid generation work flow using DEM methods for random packings and also post processing tools were created to carry out extended analyses of adsorption columns. Fully resolved packed beds were simulated to get more detailed information on gas side inhomogeneous distribution, bypass streams and near-wall effects (all these factors contribute to the total pressure drop of the packing), as well as fluid residence time distributions of random packings in columns. The current work will summarize the first results of adsorpFoam with respect to the validation using gas flow in laboratory scale random packings: The code and the procedure have been tested for spheres, mono- dispersed cylinders and cylindrical particles with size distribution. In all cases, a good agreement of the experimental results and the CFD simulations has been achieved. In a next stage of the project multi-component adsorption kinetics will be investigated, which are influenced by the local flow and temperature profile. Compared to common porous media CFD approaches a more realistic and reasonable residence time distribution can be achieved with this method.